Interventional treatment and outcome in elderly patients with stable coronary artery disease. Results from the German ALKK registry - Rittger, Harald; Hochadel, M.; Behrens, S.; Hauptmann, K. E.; Zahn, R.; Mudra, H.; Brachmann, J.; Zeymer, U. (Herz, 2014)
The number of elderly and very elderly patients undergoing percutaneous coronary interventions (PCI) is increasing. We therefore analyzed data from the German ALKK registry (Arbeitsgemeinschaft Leitende Krankenhausärzte; Working Group of Hospital Cardiologists) to determine differences in procedural features, antithrombotic treatment, and in-hospital outcome in patients with coronary artery disease (CAD) according to age in a large series of patients.The present analysis was based on the data of 35,534 consecutive patients undergoing elective PCI who were enrolled in the ALKK registry. Of these 27,145 (76.4 %) were younger than 75 years, 7,645 (21.5 %) were aged between 75 and 84 years, and 744 (2.1 %) patients were older than 85 years. Mean age was 68.5 years (60.9-74.5 years), and 25,784 patients (72.6 %) were male. Overall intraprocedural events were very low (1.1 %) and there was no significant difference between the three age groups [< 75 years (1.1 %); 75-< 85 years (1.2 %); >= 85 years (0.5 %) (p = not significant)]. Rates of in-hospital death, stroke and transient ischemic attack (TIA), as well as the combined endpoint in-hospital major adverse cardiac and cerebrovascular events (MACCE) were also very low (0.6 % vs. 0.9 % vs. 0.9 %; p < 0.001) but significantly higher in elderly patients with no further increase in the very elderly patient group.We found no differences in this registry in intraprocedural complications during elective PCI between younger and elderly patients. Although in-hospital MACCE were somewhat higher in the elderly, the overall event rate was low and thus elderly patients should not be deprived from this therapy because of age alone.
EVALuna2:12017